Does lymphadenectomy effect postoperative surgical morbidity and survival in patients with adult granulosa cell tumor of ovary?. Issue 5 (13th February 2019) - Erkılınç, Selçuk; Taylan, Enes; Karataşlı, Volkan; Uzaldı, İpek and Karadeniz, Tuğba and Gökçü, Mehmet and Sancı, Muzaffer
Abstract: Aim: To evaluate the effect of lymphadenectomy on surgical morbidity and survival in adult granulosa cell tumor (AGCT) of the ovary. Methods: Patients who underwent surgical treatment for AGCT between January 1993 and January 2016 were identified. Data were collected for patient age, menopausal status, surgical staging, lymphadenectomy, postoperative complications (anemia, wound infection, incisional hernia), length of hospital stay, follow‐up duration, site and time for recurrence, management of recurrence and vital status. Histopathological records were also evaluated for number of cellular mitosis. Results: Lymphadenectomy (pelvic–paraaortic) was performed in 53 (53%) of 98 patients. Decrease in postoperative hemoglobin level and increased wound infection and longer hospital stay were significantly higher in lymphadenectomy group ( P = 0.003, 0.043 and <0.001, respectively). Tumor stage (HR 95% CI 14.9 [2.43–92.8]) and number of mitoses >5 (HR 95% CI 14.9 [2.43–92.8]) were significantly associated with recurrence ( P = <0.001 and 0.02, respectively). Tumor stage was the only prognostic factor for predicting overall survival (HR 95% CI 8.47 [2.17–33.2]). Lymphadenectomy showed no effect on disease‐free survival and overall survival both in multivariate Cox regression analyses ( P = 0.46 and 0.69, respectively). Disease‐free survival and overall survival were similar in lymphadenectomy and no lymphadenectomy groups (Log Rank P = 0.382, 0.741, respectively). Conclusion: Lymphadenectomy had no improved effect on survival and had negative effect on surgical morbidity in patients with AGCT.